Improved production of deglucosylated platycodin D from saponins from balloon flower leaf by a food-grade enzyme using high hydrostatic pressure. Issue 10 (October 2021) - Shin, Kyung-Chul; Kim, Dae Wook; Oh, Yu Jin; Seo, Min-Ju; Na, Chae Sun; Kim, Yeong-Su
Abstract: Platycosides, saponins contained in balloon flower, which have been used as food health supplements for respiratory diseases, have diverse pharmacological effects. Platycosides exhibit better pharmacological activity by hydrolyzing their own sugars. However, to date, there have been no studies on the production of deglucosylated platycodin D suitable for food applications. In this study, Pluszyme 2000P, which was derived from Aspergillus niger, a food-grade microorganism, was used to completely convert platycoside E into deglucosylated platycodin D. For an efficient and economical production of deglucosylated platycodin D, the productivity was improved approximately 2.4 times by application of high hydrostatic pressure and the discarded balloon flower leaf was used as a substrate. As a result, deglucosylated platycodin D was produced with the highest concentration (3.49 mg/mL) and productivity (581.7 mg/L/h) reported so far. Our results contribute to functional saponin production and the related food industries. Abstract : Platycoside; Pluszyme 2000P; Food additive; Aspergillus niger ; Balloon flower; Medicinal herb.